The Helplessness Dimension of Pain Catastrophizing Mediates the Relation between PTSD Symptoms and Pain Rehabilitation Measures - Matthew Schumann; Julia Craner; Elizabeth Kacel; Eleshia Morrison; Keith Gascho; Judy Gebhard; Wesley Gilliam (Pain Research and Management)
Background. Comorbid chronic pain and post-traumatic stress disorder (PTSD) complicate the treatment of both conditions. Previous research has identified pain catastrophizing as a potentially important variable contributing to the relationship between chronic pain and PTSD. However, little is known regarding how the different dimensions of pain catastrophizing—rumination, magnification, and helplessness—uniquely contribute to the relationship between PTSD symptomatology and measures of pain outcome. Methods. 491 treatment seeking participants were admitted to a three-week interdisciplinary pain rehabilitation program between July 2016 and March 2020. The patients completed measures of pain severity, pain interference, pain catastrophizing, depressive symptoms, quality of life (QOL), and PTSD symptoms at pretreatment. Results. Parallel mediation analyses were conducted to evaluate the mediating effect of the Pain Catastrophizing Scale subscales on the relationship between PTSD symptomatology and pain-relevant variables. The helplessness subscale accounted for significant unique variance in the relationship between PTSD symptomatology and pain severity (b = 0.010, SE = 0.002, 95% CI: 0.006, 0.014), pain interference (b = 0.004, SE = 0.002, 95% CI: 0.001, 0.008), and mental health QOL (b = −0.117, SE = 0.031, 95% CI: −0.179, −0.059), while the rumination and magnification subscales had no significant influence. Conclusions. Pain catastrophizing is a multifaceted construct. These results suggest that the helplessness dimension of pain catastrophizing may be the primary target when treating patients with comorbid chronic pain and PTSD symptoms. This study represents the first to evaluate the influence of the individual dimensions of pain catastrophizing on the relationship between PTSD symptomatology and chronic pain outcome.